2018
DOI: 10.1007/s10126-018-9834-4
|View full text |Cite
|
Sign up to set email alerts
|

The Plant Alkaloid Camptothecin as a Novel Antifouling Compound for Marine Paints: Laboratory Bioassays and Field Trials

Abstract: The extensive use of copper and booster biocides in antifouling (AF) paints has raised environmental concerns and the need to develop new AF agents. In the present study, 18 alkaloids derived from terrestrial plants were initially evaluated for AF activity using laboratory bioassays with the bryozoan Bugula neritina and the barnacle Balanus albicostatus. The results showed that 4 of the 18 alkaloids were effective in inhibiting larval settlement of B. neritina, with an EC range of 6.18 to 43.11 μM, and 15 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 75 publications
0
8
0
2
Order By: Relevance
“…La mayoría de los resultados satisfactorios se observaron en ocho especies de la familia Fabaceae, pertenecientes a ocho géneros diferentes (Stupak, et al, 2003;Zhou, et al, 2009;Qian, et al, 2010;Feng, et al, 2018;Agostini, et al, 2019;Clasen y Kesel, 2019). La familia Fabaceae, también llamada Leguminosae, es una de las familias botánicas más grandes e importantes (Di Stasi e Hiruma-Lima, 2002), y está compuesta por aproximadamente 19.000 especies distribuidas en 695 géneros (Giulietti, et al, 2005).…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…La mayoría de los resultados satisfactorios se observaron en ocho especies de la familia Fabaceae, pertenecientes a ocho géneros diferentes (Stupak, et al, 2003;Zhou, et al, 2009;Qian, et al, 2010;Feng, et al, 2018;Agostini, et al, 2019;Clasen y Kesel, 2019). La familia Fabaceae, también llamada Leguminosae, es una de las familias botánicas más grandes e importantes (Di Stasi e Hiruma-Lima, 2002), y está compuesta por aproximadamente 19.000 especies distribuidas en 695 géneros (Giulietti, et al, 2005).…”
Section: Resultados Y Discusiónunclassified
“…Entre los resultados obtenidos en los artículos, se identifican bacterias (microfouling) e invertebrados (macrofouling) como organismos objetivos para la inhibición. El 24% de los resultados antiincrustantes satisfactorios se centraron en el microfouling (Xu, et al, 2005;Qian, et al, 2010;Salta, et al, 2013;Pérez, et al, 2014;Nandhini y Revathi, 2016;Moodie, et al, 2018;Agostini, et al, 2019;Nadir, et al, 2020), el 61% en el macrofouling (Takasawa, et al, 1990;Etoh, et al, 2002;Stupak, et al, 2003;Goransson, et al, 2004;Angarano, et al, 2007;Pérez, et al, 2007;Feng, et al, 2009;Zhou, et al, 2009;Qian, et al, 2010;Bellotti, et al, 2014;Cui, et al, 2014;Huang, et al, 2014;Pérez, et al, 2014;Bogdan, et al, 2018;Feng, et al, 2018;Clasen y Kesel, 2019), y el 14% en ambas comunidades. En el Anexo 2 se presenta la lista de organismos inhibidos por la acción de extractos, compuestos o moléculas derivadas de plantas terrestres.…”
Section: Resultados Y Discusiónunclassified
“…As the barnacle grows, its edges will destroy the anticorrosion layer on the hull surface, thereby accelerating the hull corrosion [ 4 ]. As shown in Figure 1 [ 5 ], when the hull surface is attached, fouling organisms will corrode the hull surface and increase the roughness of the hull surface, thereby reducing the speed of the ship [ 6 , 7 , 8 ], increasing fuel consumption and greenhouse gas emissions [ 9 , 10 ]. In recent years, with the rapid development of offshore industries such as submarine oil and marine power generation, the damage of marine fouling organisms to man-made facilities has become more severe.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, coatings containing camptothecin derived from terrestrial plants have been found to be effective in laboratory bioassays and field trails. 42 However, the complex structure and high cost of camptothecin make it challenging for commercial marine antifouling coating application. Coatings consisting of tannins and nonreactive polymers such as vinyl resin or chlorinated rubber have also been reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Natural product antifoulants (NPAs) extracted from natural sources are an ideal choice for antifouling coatings because they exhibit excellent eco-friendliness. Until now, butenolide, terpenoids, camptothecin, and phenolic compounds from marine bacteria, algae, and terrestrial plants have been reported to effectively inhibit the attachment of diverse fouling organisms. Moreover, NPA-based antifouling coatings have also been explored in the past few years. For instance, coatings containing camptothecin derived from terrestrial plants have been found to be effective in laboratory bioassays and field trails .…”
Section: Introductionmentioning
confidence: 99%